Cancer Rehabilitation Fact Sheet in Korea - Jin A Yoon; Bo Young Hong (Annals of Rehabilitation Medicine, 2022)
Cancer rehabilitation aims to enable patients to maximize their physical, social, psychological, and vocational functions within the limits that arise during the course of the disease and its treatment. According to recent domestic studies, most patients report one or more physical problems during or after cancer treatment. This review presents the latest updates on cancer-related rehabilitation issues. Cancer rehabilitation in Korea still faces various barriers, including a lack of awareness, problems with the healthcare delivery system, and high costs, and recognizing the need for rehabilitation during cancer treatment varies among patients and even physicians. Hence, an appropriate cooperative referral system for cancer rehabilitation requires improvement. We herein review the current status of and barriers to cancer rehabilitation in South Korea to resolve the issues of domestic cancer rehabilitation.